2021
DOI: 10.1101/2021.05.03.442446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation of SIV resistant T cells and Macrophages from Nonhuman Primate Induced Pluripotent Stem Cells with Edited CCR5 locus

Abstract: Adoptive therapies with genetically modified somatic T cells rendered HIV resistant have shown promise for AIDS therapy. A renewable source of HIV resistant human T cells from induced pluripotent stem cells (iPSCs) would further facilitate and broaden the applicability of these therapies. Here, we report successful targeting of the CCR5 locus in iPSCs generated from peripheral blood T cells (T-iPSCs) or fibroblasts (fib-iPSCs) from Mauritian Cynomolgus macaques (MCM), using CRISPR/Cas9 technology. We found tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…To functionally delete CCR5 in macaque embryos, we designed gRNAs that would encompass a 24-bp deletion that Frontiers in Genome Editing frontiersin.org has previously been shown to be essential for expressing CCR5 in non-human primates (Chen et al, 1998). Our previous cell-based editing experiments confirmed successful on-target editing with functional deletion of the CCR5 gene in both human (Kang et al, 2015) and macaque (D'Souza et al, 2022) iPSCs. A schematic diagram of the targeting region is shown in Figure 1A.…”
Section: Wgs Of Individual Blastomeres Produces Variable Sequence Cov...mentioning
confidence: 77%
“…To functionally delete CCR5 in macaque embryos, we designed gRNAs that would encompass a 24-bp deletion that Frontiers in Genome Editing frontiersin.org has previously been shown to be essential for expressing CCR5 in non-human primates (Chen et al, 1998). Our previous cell-based editing experiments confirmed successful on-target editing with functional deletion of the CCR5 gene in both human (Kang et al, 2015) and macaque (D'Souza et al, 2022) iPSCs. A schematic diagram of the targeting region is shown in Figure 1A.…”
Section: Wgs Of Individual Blastomeres Produces Variable Sequence Cov...mentioning
confidence: 77%
“…To confirm that CRISPR/Cas9-targeted CCR5 edits also protects macaque cells from SIV infection, we generated iPSCs from MCM fibroblasts, edited their CCR5 locus, and derived T cells and macrophages. We found that T cells and macrophages produced from CCR5-edited fibroblast-derived iPSCs did not support replication of the CCR5 T cell-tropic SIVmac239 and macrophagetropic SIVmac316 simian immunodeficiency viruses, thus validating our CCR5 editing strategy [76].…”
Section: Editing Ccr5 In Mauritian Cynomolgus Macaque Embryosmentioning
confidence: 80%
“…High expression of CCR5 causes tumor cell migration and vascular invasion, which can result in distant metastasis of several types of tumor such as in breast cancers [7][8][9] , hepatocellular carcinoma [10] and prostate cancers [11][12][13] . Given its prominence in the regulation of immunity, several clinical trials targeting CCR5 are under way, involving cancers [7,13] , COVID-19 [14] ,immune de ciency diseases like HIV [15][16][17][18] , etc.…”
Section: Introductionmentioning
confidence: 99%